Evaluation of the Sensitivity and Specificity of MiRNAs in Discriminating Oral Squamous Cell Carcinoma: A Systematic Review and Meta-analysis - Ali Salehi; Homa Mirzaei; Zahra Pourgholi Takrami; Mahtab Salehi; Asal Moravej (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Approximately 90% of all oral malignant tumors are squamous cell carcinomas. This study aims to evaluate the sensitivity and specificity of miRNAs in discriminating oral squamous cell carcinoma. Material and methods: There are many international databases such as PubMed, Scopus, Science Direct, ISI, Web of Knowledge, Embase, and many other databases in oral squamous cell carcinoma searched until May 2023. Data analysis using STATA/MP. V17 software was done in 95% confidence intervals. Effect size (sensitivity and specificity) were calculated using a fixed effect model with an inverse-variance method. Results: The full text of 25 studies was reviewed; finally, 17 studies were selected according to the objectives of the present study and included in the meta-analysis. The sensitivity and specificity of miRNAs in diagnosing OSCC were 77% (ES, 77% CI; 70%, 84%; p<0.01) and 80% (ES, 80% CI; 73%, 87%; p<0.01), respectively. Test of group differences showed no significant difference between sensitivity and specificity of the salivary, blood, and serum miRNAs in diagnosing oral squamous cell carcinoma (OSCC) (p>0.05). Conclusions: Based on the meta-analysis of the present study, the diagnostic accuracy of miRNAs for the diagnosis of OSCC is high; Blood, saliva, and serum miRNAs had similar sensitivity and specificity.